Practices of Protest in the Conditions of the Developing Academic Capitalism - A. E. Geger; S. V. Lyashko; A. V. Klyuev; G. I. Saganenko (Высшее образование в России)
The article focuses on the problem of professional motivation of University teaching staff in the context of developing “academic capitalism” and presents the results of the empirical study carried out by the authors at the North-Western Institute of management of RANEPA in March–June 2020. Based on the data obtained, it is revealed that teachers, experiencing deep deprivation of their social needs – the needs for respect, recognition and honor, are trying to find their place in the modern system, get out of the grip of double pressure, on the one hand, from the administration, which purposefully imposes rating systems and effective contracts, increasing competition between teachers, and on the other hand – students, who are now positioned as clients of universities. In the context of developing academic capitalism, teachers choose one of two adaptation strategies: 1) conformism as an opportunity to integrate into a constantly changing situation; 2) the practice of quiet protest as an opportunity to demonstrate the inefficiency of the entrepreneurial model of higher education, at least in its current version, and 3) neutral position to protect the classical values of the academic community.